2011
DOI: 10.1007/s13105-011-0120-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the melanocortin-3 receptor Thr6Lys and Val81Ile genetic variants on body composition and substrate oxidation in Chilean obese children

Abstract: Mice genetically deficient in the melanocortin-3 receptor gene are characterized by normal body weight, increased body fat, mild hypophagia, reduced locomotor activity, and increased respiratory quotient compared with wild-type mice. In humans, the 6Lys-81Ile haplotype of melanocortin-3 receptor (MC3R) gene has been associated with childhood obesity, higher body fat percentage, and reduced fat oxidation compared to non-carriers. The aim of this study was to evaluate the association between MC3R 6Lys-81Ile hapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Like MC4R, melanocortin-3 receptor (MC3R) has been found to play a role in energy balance. Previous studies have reported several common and rare variants in MC3R that inconsistently associate with obesity (11)(12)(13)(14)(15)(16)(17). MC3R is thought to coordinate feeding-related behaviors and glucose metabolism through the action of the melanocortin signaling pathway in the brain (18 -21).…”
mentioning
confidence: 99%
“…Like MC4R, melanocortin-3 receptor (MC3R) has been found to play a role in energy balance. Previous studies have reported several common and rare variants in MC3R that inconsistently associate with obesity (11)(12)(13)(14)(15)(16)(17). MC3R is thought to coordinate feeding-related behaviors and glucose metabolism through the action of the melanocortin signaling pathway in the brain (18 -21).…”
mentioning
confidence: 99%
“…Consistent with knockout mouse models [36], glucose oxidation was increased and lipid oxidation decreased in T6K+V81I carriers [69, 71]. T6K+V81I variant carriers may also have greater difficulty losing weight, consistent with the “metabolically thrifty” phenotype [72, 73].…”
Section: Human Studiesmentioning
confidence: 73%
“…Two studies found no differences in energy intake between genotypes [52, 59], and in a third, the association no longer was significant when the data were examined separately by race [64]. Additionally, no significant differences were seen in resting energy expenditure [59, 64, 69], total energy expenditure [64, 71], respiratory quotient [59, 64], or physical activity [52, 64, 71, 72]. …”
Section: Human Studiesmentioning
confidence: 99%